Genome Sequence of Rhizobium etli CNPAF512, a Nitrogen-Fixing Symbiont Isolated from Bean Root Nodules in Brazil - Fauvart, Maarten (American Society for Microbiology, 2011)
Rhizobium etli is a Gram-negative soil-dwelling alphaproteobacterium that carries out symbiotic biological nitrogen fixation in close association with legume hosts. R. etli strains exhibit high sequence divergence and are geographically structured, with a potentially dramatic influence on the outcome of symbiosis. Here, we present the genome sequence of R. etli CNPAF512, a Brazilian isolate from bean nodules. We anticipate that the availability of genome sequences of R. etli strains from distinctly different areas will provide valuable new insights into the geographic mosaic of the R. etli pangenome and the evolutionary dynamics that shape it.